64. Traditional to Online Media in China and Korea: Unfulfilled promise - Motlik, Scott (International Review of Research in Open and Distributed Learning, 2008)
The governments of China and South Korea have supported the development of distance education both legislatively and financially. The use of traditional media for this purpose has been successful in both countries, though the evolution to Internet-based education has been only partially successful. This report describes this process in terms of uncritical application of western distance education technology and methodology in environments that are unsuitable for them. Until these issues are addressed, it is suggested Web-based educational education approaches in South Korea and China will remain unreliable, and will fail to provide a complete service to students.